Changes in Degree Centrality of Network Nodes in Different Frequency Bands in Parkinson’s Disease With Depression and Without Depression - Liao, Haiyan; Yi, Jinyao; Cai, Sainan; Shen, Qin; Liu, Qinru; Zhang, Lin; Li, Junli; Mao, Zhenni; Wang, Tianyu; Zi, Yuheng; Wang, Min; Liu, Siyu; et al. (Frontiers in Neuroscience, 2021)
Background: Depression induces an early onset of Parkinson’s disease, aggravats dyskinesia and cognitive impairment, and accelerats disease progression. However, it is very difficult to identify and diagnose PD with depression (PDD) in the early clinical stage. Objective: To explore degree centrality (DC) changes between patients with Parkinson’s disease (PD) with depression (PDD) and without depression (PDND); and to find the key brain hubs involved with depression in PD patients. Methods: One hundred and four PD patients and fifty-four healthy controls underwent brain resting state functional magnetic resonance imaging (RS-fMRI). The Data Processing and Analysis of Brain Imaging (DPABI) and Resting State Functional Magnetic Resonance Data Analysis Toolkit (REST) were used for processing and statistical analysis. The DC value of each frequency band was calculated. One-way analysis of variance and a two-sample t-test for post-hoc comparison were used to compare the differences of the DC values in different frequency bands among PDD, PDND, and healthy control group. Gaussian random field was used for multiple comparison correction. Pearson correlation analysis was performed between each individual's DC map and clinical indicators. Results: The DC value of different brain regions changed in PDD and PDND in different frequency bands. The prefrontal lobe, limbic system, and basal ganglia were the main brain regions involved. PDD patients showed a wider range and more abnormal brain areas in the slow-4 frequency band (0.027-0.073 Hz) compared to the healthy controls. PDD showed a decreased DC value in the medial frontal gyrus, bilateral cuneus gyrus, right lingual gyrus, bilateral supplementary motor area, bilateral superior frontal gyrus, and left paracentral lobule, but an increased DC value in the bilateral brainstem, midbrain, bilateral parahippocampal gyrus, cerebellum, left superior temporal gyrus, bilateral insula, left fusiform gyrus, and left caudate nucleus in the traditional frequency band (0.01-0.08Hz) compared to PDND patients. PDND patients displayed more abnormal functions in the basal ganglia in the slow-4 frequency band. Conclusions: The DC changes in PDD and PDND are frequency-dependent and frequency-specific. The medial frontal gyrus, supplementary motor area, and limbic system may be the key hubs for depression in Parkinson's disease.